A Systematic Review of Oxidative Stress and Safety of Antioxidants in Diabetes: Focus on Islets and Their Defense - Udayakumar Karunakaran; Keun-Gyu Park (Diabetes & Metabolism Journal, 2013)
A growing body of evidence suggests that hyperglycemia-induced oxidative stress plays an important role in diabetic complications, especially β-cell dysfunction and failure. Under physiological conditions, reactive oxygen species serve as second messengers that facilitate signal transduction and gene expression in pancreatic β-cells. However, under pathological conditions, an imbalance in redox homeostasis leads to aberrant tissue damage and β-cell death due to a lack of antioxidant defense systems. Taking into account the vulnerability of islets to oxidative damage, induction of endogenous antioxidant enzymes or exogenous antioxidant administration has been proposed as a way to protect β-cells against diabetic insults. Here, we consider recent insights into how the redox response becomes deregulated under diabetic conditions, as well as the therapeutic benefits of antioxidants, which may provide clues for developing strategies aimed at the treatment or prevention of diabetes associated with β-cell failure.